The effect of the core material of the Rogowski coil sensor on the sensitivity of the magnitude of partial discharge. Issue 1 (January 2021) - Waldi, E P; Winarta, F P; Lestari, A I; Fernandez, R; Laksono, H D; Aulia,; Rajab, A; Nawawi, Z; Ahmad, M H; Hozumi, N
Abstract: The Rogowski Coil sensor is one of the sensors used to detect aging insulation, which is marked by the occurrence of Partial Discharge. Aging is damaged, which fails power tools when operated. If the insulation is aging and even causing damage, the distribution of electrical energy will be disrupted. This research presents two types of Rogowski Coil sensor core materials to detect Partial Discharge with the same number of turns. The number of turns is 5. The first sensor is a sensor with a ferromagnetic core and the second sensor is a sensor with a non ferromagnetic core. The test of the sensor is carried out by using a magnitude test using a charge calibrator as an imitation of Partial Discharge. The magnitude of the Partial Discharge read by the sensor uses a digital oscilloscope with an impedance of 50 Ohm. Measurement results compared to commercial sensors. The measurement results read by the oscilloscope found that the type of sensor core influences the magnitude value of Partial Discharge. The magnitude of the Partial Discharge sensor with a ferromagnetic core is greater than that of a sensor with a non ferromagnetic core. However, both results are much smaller than the commercial sensor even though the digital oscilloscope can read them.